Tensions and opportunities in the roles of senior public health officials in Canada: A qualitative study. Issue 10 (October 2022) - Cassola, Adèle; Fafard, Patrick; Nagi, Ranjana; Hoffman, Steven J.
Highlights: Chief Medical Officers of Health variously act as advisors, managers, and communicators. As public servants, tensions exist between their government- and public-facing roles. Officials use political acumen and pragmatism to navigate these tensions. The role's design differs across jurisdictions and affects incumbents' pathways to impact. When designing the role, governments must balance trade-offs and consider desired outcomes. Abstract: Although public health emergencies like the COVID-19 pandemic thrust senior public health officials into the spotlight, their day-to-day roles remain misunderstood and under-examined. In jurisdictions that follow the Westminster system of government such as Canada, the United Kingdom, and Australia, Chief Medical Officers of Health (CMOHs) are typically senior public servants who are simultaneously positioned as public health professionals with independent expertise, senior advisors to an elected government, and designated protectors of the public health interest. Using Canada's federal and provincial CMOHs as case studies of this role in Westminster governments, we analyzed in-depth key informant interview data to examine how CMOHs navigate the tensions among their duties to the government, profession, and public in order to maximize their public health impact. We demonstrate that CMOHs are variously called upon to be government advisors, public health managers, and public communicators, and that the different emphasis that jurisdictions place on these roles shapes the tools and pathways through which CMOHs can influence government action and public health. We also elucidate the tensions associated with having CMOHs positioned within the senior levels of the public service and the strategies these officials use to balance their internal- and external-facing roles. Finally, we highlight the trade-offs among different institutional design options to inform decisions about the structure of the CMOH position in different contexts.